Parenting style of the Malaysian undergraduate students in the Faculty of Education, Universiti Teknologi Malaysia - Ehsan Jaberi Motlagh, 1984-; Zainudin Abu Bakar, supervisor; Fakulti Pendidikan (2012)
Thesis (Sarjana Pendidikan (Psikologi Pendidikan)) - Universiti Teknologi Malaysia, 2012